PENGARUH SURAT BERHARGA YANG DIMILIKI / (INVESTMENT IN SECURITIES) NON BANK DAN BANK LAIN TERHADAP LABA BERSIH BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH PERIODE 2008-2021 - Kusumaningrum, Ria; Mursyidah, Azizah; Nisa, Sadidatun; Iskandar, Lina (SAHID BANKING JOURNAL, 2023)
The Bank prepares a fund placement strategy based on the allocation plan by taking into account the policies outlined with the aim of achieving a good level of profitability and maintaining public trust by maintaining a safe liquidity position. By combining these two desires, the allocation of bank funds must be directed in such a way that when necessary, all customer interests can be met. This can be done through investments made by sharia banks (in the form of placements with other banks or investments in securities and also from financing). The profit returns expected by Islamic banks come from profit sharing, profit margins, rent and others. Based on research conducted, Securities Owned / (Investment in Securities) of Non-Banks and Other Banks have an influence on the Net Profit of Sharia Commercial Banks and Sharia Business Units for the 2008-2021 Period. However, the positive influence mentioned above must still be balanced with the importance of the presence and existence of Sharia Commercial Banks and Sharia Business Units, namely as financing institutions that invest directly through mudharabah, murabahah and musyarakah.